Liverpool Telecare Pilot: case studies - Nigel Barnes (Journal of Innovation in Health Informatics, 2006)
Telecare services use information and communications technology (ICT) to support the provision of care to people in their own homes. This paper describes a pilot telecare service employed by Liverpool (UK) City Council to support a sample of their frail and elderly social services users. The pilot has been running for over two years and has been deployed for 21 individuals in Liverpool. In this paper we present the pilot system and provide real example cases which help to illustrate the benefits of such a system.